48 Evaluating community health practitioners perspective of the heart failure pathway. (October 2018) - Lennon, E; Kalra, P; Reily, R; Kernan, R; Gallagher, J; Ledwidge, M; Keane, C; Cowie, M; McDonald, K; Walshe, M
Abstract : Background: There is growing interest in building community capacity to manage Heart Failure (HF). As well as patient/caregiver engagement, the Community Pharmacist (CP) and General Practitioner (GP) play a central role in the community care of HF. As part of a care-pathway mapping programme for HF, we aimed to describe GP/CP perspectives and identify areas for development. Purpose/method: We administered an internally validated questionnaire to eighty CPs and GPs of consecutive consenting HF patients admitted with an acute decompensation. These patients were participating in a prospective care-pathway mapping project in the Heart Failure Unit of a large teaching hospital. Questionnaires were conducted by post. The responses were then analyzed. Response rates were 57.5% (46) and 40% (32) of GPs and CPs respectively. Results: In terms of enablers of better community HF care, 93%(43) of GPs felt that they could improve diagnosis and management of HF in the community if they had routine access to Natriuretic Peptide testing and the support of same-day HF services. Eighty-five percent (39) stated that if they had access to Echocardiography they would be better enabled to screen for heart failure. A further perceived barrier to optimal HF care within the community amongst 83% (38) of GPs was the patient's own lack of HF education and understanding of their diagnosis. Furthermore, 67% (31) of GPs felt that there should be an increase in the number of outpatient HF clinics. Almost half of CPs, 45% (14) did not have access to information regarding the patient's diagnosis of HF, requiring confirmation before medicines management. Prescription changes were needed in half of cases (16) and just under half of pharmacists reported spending 30–60 min seeking information from medical and healthcare professionals regarding HF issues. Changes related to discharge prescription errors, omitted regular medications, inappropriate medications and incorrect dosages. Conversely, 45% (14) of CPs reported no access t the hospital team regarding medication queries yet, almost half of CPs (16) reported that GPs did not have adequate information regarding the HF plan. Most 72%(23) of CPs felt that it should be standard of care for teams making a medication change on a HF patient's script, to communicate this change and reason for it to the community pharmacist. Conclusion: These results describe significant gaps in the community HF care pathway amongst healthcare professionals with the most frequent HF patient contact. Most of the barriers relate to information flows, care coordination and access to diagnostics with negative consequences on community care management and resources. Identifying areas for targeted improvement along each stage of this pathway will improve outcomes, efficiencies and the experience of care for HF patients.